PENATAAN PEDAGANG KAKI LIMA KULINER UNTUK MEWUJUDKAN FUNGSI TATA RUANG KOTA DI KOTA YOGYAKARTA DAN KABUPATEN SLEMAN* - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Even though street vendors in Yogyakarta and Sleman bring in a huge amount of income for the city budget, they are often ignorant to public space regulations. This research aims to find an arrangement model for street vendors in accordance to the city spatial plan.